2004
DOI: 10.1002/ejic.200300617
|View full text |Cite
|
Sign up to set email alerts
|

Aminomethyl and Aminoacetyl Complexes of Palladium(II), Platinum(II), Iron(II) and Rhenium(I) with N‐Phthaloyl as Amino Protecting Group and Mechanistic Studies on the Palladium‐Catalyzed Amidocarbonylation

Abstract: New aminomethyl and aminoacetyl complexes with N‐phthaloyl as the amino protecting group were synthesised by oxidative addition of N‐phthaloylmethyl or ‐acetyl halide to carbonylmetallates or to Pd(PPh3)4 or [Pt(C2H4)(PPh3)2] to give [Re{C(O)CH2N‐phthaloyl}(CO)5] (1), [FeCp(CH2N‐phthaloyl)(CO)2] (2), [FeCp{C(O)CH2N‐phthaloyl}(CO)2] (3), trans‐[PdBr(CH2N‐phthaloyl)(PPh3)2] (4) and trans‐[Pd{C(O)CH2N‐phthaloyl}(X)(PPh3)2] (X = Br, Cl; 5, 6). The bis(phosphane) complexes [Pd(CH2N‐phthaloyl)(X)(R2PCH2CH2PR2)] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…A rather unusual phthalimidomethyl Fp complex was reported by Enzmann et al [96] after they reacted the Fp anion with bromomethylphthalimide (Scheme 30). This complex was prepared as part of a study to understand N-protected groups and Scheme 29. their role and use as catalysts in amidocarbonylation reactions for potential use in peptide synthesis.…”
Section: Fe-c (Sp 3 ) Bond Formationmentioning
confidence: 88%
See 1 more Smart Citation
“…A rather unusual phthalimidomethyl Fp complex was reported by Enzmann et al [96] after they reacted the Fp anion with bromomethylphthalimide (Scheme 30). This complex was prepared as part of a study to understand N-protected groups and Scheme 29. their role and use as catalysts in amidocarbonylation reactions for potential use in peptide synthesis.…”
Section: Fe-c (Sp 3 ) Bond Formationmentioning
confidence: 88%
“…Phthaloyl chloride was also reacted with Fp anion using a known procedure. Although Beck and coworkers also prepared [96] an Fp phthaloylacetyl complex from Fp anion and phthaloylacetyl chloride (Scheme 66). The N-protected aminoacetyl Fp complex could be useful for the synthesis of peptides.…”
Section: Scheme 35mentioning
confidence: 95%
“…[63] Model studies with N-(chloromethyl)phthalimides revealed the palladium-catalyzed activation of an intermediate a-halo N-acyl amine. [64] Subsequent carbonylation of the resulting alkyl palladium species leads directly to a wide range of amino acids, such as aryl glycines and hydantoins. [65] …”
Section: Carbonylations Of Alkyl Electrophilesmentioning
confidence: 99%
“…Note the rather high Pt-P coupling constant, which in trans-Pt II (PPh 3 ) 2 complexes is usually in the 2500-3000 Hz range; higher values have, however, also been reported. [12,15] The FAB + mass spectrum of 9 (see Experimental section) shows only a weak peak (ca. …”
Section: Structure and Characterization Of Trans-[pt(pph 3 ) 2 (Mtc) mentioning
confidence: 99%